Remembering Jews in Poland: the encounter between Warsaw's POLIN Museum and rural memories of Jewish absence – divergent aims and needs. Issue 3 (3rd July 2019) - Kubica, Aleksandra; Van de Putte, Thomas
ABSTRACT: The POLIN Museum runs a traveling exhibition ( Museum on Wheels) which has visited places in rural Poland since 2014. The exhibition's aim is to teach about 'the centuries of coexistence of Jewish and Polish culture.' The Holocaust is one of the elements presented but is not central. Our content and lexicometric analysis of interviews with visitors from five towns visited by MoW in 2015 and 2016 indicates that the needs articulated by visitors differed from POLIN's agenda. We show that the Holocaust and Jewish absence in the rural Poland of the present were the most prominent topics appearing, not the continuity of Jewish life and culture. Although it was not its central aim, the three days visit of MoW has created opportunities for local communities to address the void left after the Holocaust. For our analysis, we traced the museum's discourse on the one hand and the 'discourse of absence' of the visitors on the other hand on the basis of keywords. From these two sets of keywords, we quantitatively mapped the prominence of both discourse and combined it with a more qualitative content analysis of specific segments of the interviews of which our corpus is composed.